Molave Youth Home at Payatas Quezon City children at risk and CICL facility improvement through aid programs - Ragadio, Lyndzy Sarah S. (College of Architecture, University of the Philippines Diliman, 2013)
“ I know that its bad but we had to do it so we can it.” –child detained in the Davao city jail In the Philippines, the problems with the children at risk and children in conflict with the law (CICL) are related to social issues. Juvenile delinquency becomes a means of survival especially for those who are less fortunate. Current trends in architectural research covers only to rehabilitation programs, thus providing designs for rehabilitation facilities. But this becomes only a temporary solution. Oftentimes, after their release, they go back to vicious cycle of poverty and crime because of the need to support themselves (Soriano,2001). And there is currently an insufficient number of existing facilities for such minors who are detained and a lot of those facilities are unfit for the children. This study proposes the use of an after-care program to reduce recidivism and to guide the former juvenile delinquents, their family and the community. The study used the strengths of the immediate community to make the program, sustainable and feasible. The new Molave Youth Home will serve as a shield for the former juvenile as they are finally reintegrated to the society. The thesis provided spaces that the rehabilitative and responsive to aftercare program that they need. Furthermore, the enhance spaces, ambiance and layout of the project aims to change the way they view their lives and break the cycle of crime that seizes them.